Peran Pembiayaan Kesehatan dalam Mendukung Kesiapan Transformasi Layanan Kesehatan - Rizkiyatul Amalia; Eliyah; Arief Azhari Ilyas (Poltekkes Kemenkes Semarang, 2025)
Tuberculosis (TB) remains a serious global health problem, especially in high-prevalence countries like Indonesia. Despite decades of efforts, TB cases in Indonesia have not shown a significant decline. Transformation of TB health services is needed to improve universal access to quality diagnosis and treatment, which relies heavily on health financing readiness. This study aimed to explore the association of health financing with readiness for TB health service transformation. This study used a cross-sectional design with a quantitative approach involving a survey of 99 TB patients at five health centers in Central Java. Primary data were collected through a questionnaire evaluating health financing and health service transformation, and analyzed using the SmartPLS method. The results showed that health financing significantly influenced readiness for health service transformation (T-statistic = 3.180; p = 0.002). TB financing in Indonesia is dominated by international donor funding such as the Global Fund and the BPJS Health scheme, but challenges remain in ensuring adequate allocations for promotive, preventive, and rehabilitative aspects. Resource disparities between hospitals and health centers result in inequities in TB financing and treatment outcomes. This study underscores the need for increased budget allocations to puskesmas and improved financing mechanisms to support more efficient and responsive TB health service transformation. A focus on sustainable financing and capacity building of health workers is important to achieve effective and sustainable health service transformation.